Prunus armeniaca L. cv. Hacihaliloglu Fruits Extracts Prevent Lipid Peroxidation and Protect the Unsaturated Fatty Acids in the Fenton Reagent Environment - Ozsahin, Ayse Dilek; Yilmaz, Okkes (Asian Journal of Chemistry, 2010)
This study investigated protective effects of the Prunus armeniaca L. cv. Hacihaliloglu fruits extract on the unsaturated fatty acids and the prevention of lipid peroxidation formation in the Fenton reagent environment. Lipid peroxidation level in the Fenton R group significantly high compared to control group. but lipid peroxidation in the apricot fruit extract groups significantly decreased according to the Fenton R group (p<0.0001). In addition, it was determined that apricot extracts had scavenging effect on the DPPH (alpha,alpha-diphenyl-beta-picrylhydrazyl) radical depending on the increase in flavonoid concentration. The fatty acid levels in the Fenton R group were lower than the control group (p <0.001). However, fatty acid levels in the apricot fruit extract groups were higher than the Fenton R group (p < 0.001). Present results confirm that the apricot fruit extracts decrease lipid peroxidation level in the Fenton reagent environment and protects markedly unsaturated fatty acids in the environment with radical sourced oxidations. The examined apricot varieties were found to contain fructose, glucose, sucrose, beta-sitosterol, alpha-tocopherol, stigmasterol, vitamin D, vitamin K, ergosterol and polyphenols such as catechin, rutin, resveratrol and myricetin.
Keywords: Apricot; Lipid peroxidation; Fatty acids; Flavonoids; alpha,alpha-Diphenyl-beta-picrylhydrazyl; (DPPH)